Srpski - Stričević, Ružica; Srpski, Srpski; Vujadinović - Mandić, Mirjam; Sokolović, Dejan (Journal of Agricultural Sciences (Belgrade), 2021)
It is well known that permanent grasslands have developed mechanism of survival of abiotic stresses such as hight air tepmerature or droughts. Due to air temperature increase, longer growing seasons and erratic rainfalls in last two decades, natural grasslands like meadows or pastures grow in unfavourable climatic condition, that disable regeneration. According to the regional climate models less favorable conditions for plant growth are projected in many regions. The aim of this work is to assess the impact of climate change on water requirement of grasslands in Serbia. Five locations were selected: Rimski Šančevi, Valjevo, Kragujevac, Negotin and Leskovac. To analyse future climatic conditions, results of ensembles of nine regional climate model from EURO-CORDEX database were used. As the most probable value, the median of scores obtained for each ensemble member were considered. Period 1986-2005 was used as the reference. The time slice in future periods are: 2016-2035 (near future), 2046-2065 (mid century) and 2081-2100 (end of century). Analsyes were made for two scenarios of GHG emmisions RCP4.5 and RCP8.5. Permanent grasslands will be more prone to drought risks in future. Water shortage could be expected at the end of May, when water stored in the soil depleted with duration of drought till the September's heavy rains. According to the both scenarios, increment of water requirement of 7 % could be expected in a near future. Scenario RCP4.5 projects increase in water requirement in the range of 10.7 - 24.2 % from mid to end of century. Less favourable, but more realistic scenario RCP8.5 projects water needs increment in range of 4 – 14 % in mid century and 28.4 - 41.9 % toward the end of century. As permanent grasslands are a collection of different species dominated by grass representatives, the expected responses to droughts in the future will come the most likely from them. Forsed summer dormancy will be prolonged due to hormonal regulations. Recent research indicates that drought resistance will be developed through natural diversity and the spread of species resistant to high temperatures and water scarcity.
Keywords: permanent grasslands, water shortage, climate change